Ready access to benzannulated [5,5]-oxaspirolactones using Au(III)-catalyzed cascade cyclizations - Mankad, Yash; Thorat, Sagar S.; Das, Pronay; Krishna, Gamidi Rama; Kontham, Ravindar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
This work showcases an unprecedented Au(III)-catalyzed cascade cyclization of 2-(4-hydroxyalkynyl)benzoates to access benzannulated [5,5]-oxaspirolactones related to biologically active natural products. This reaction proceeds through an initial 5-endo-dig mode of hydroalkoxylation of the alkynol segment to give the oxocarbenium species (via cyclic enol-ether) followed by the addition of carboxylate onto the oxocarbenium that delivers the oxaspirolactone scaffold. While testing this method's scope, we found that the steric and electronic environment of the hydroxyl group could alter the reaction pathway that delivers isochromenone through a competitive 6-endo-dig mode of attack of the carboxylate onto the tethered alkyne.

Regioselective synthesis of benzannulated [5,6]-oxaspirolactones via Cu(II)-catalyzed cycloisomerization of 2-(5-Hydroxyalkynyl)benzoates - Thorat, Sagar S.; Shimpi, Sagar P.; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2023)
Spiroketals and oxaspirolactones are widely found in biologically active natural products, serving as important structural motifs. In this study, we present a Cu-(II)-catalyzed cascade cycloisomerization of 2-(5-hydroxyalkynyl)-benzoates, enabling the regioselective synthesis of benzannulated [5,6]-oxaspirolactones containing an isochromen-1-one moiety. This strategy offers a rapid and efficient approach to access a diverse array of benzannulated [5,6]-oxaspirolactones. The methodology presented here showcases a broad substrate scope, delivering good yields and scalability up to gram scale. The structures of the oxaspirolactones were unequivocally confirmed through single-crystal X-ray analysis and by analogy using H-1 and C-13-H-1 NMR data.
Keywords: Construction; Isocumarins; Strategies